CPR Guidelines and Hypothermia Improve Survival - Alexander, Walter (MD Conference Express, 2006)
Sudden cardiac arrest is a major public health concern, with more than 400,000 deaths annually in the United States alone. A patient’s chance of survival drops by 7–10%/min when CPR is delayed after cardiac arrest. Widespread adherence to the new Advanced Cardiac Life Support/Emergency Cardiac Care guidelines for CPR and the increased use of therapeutic hypothermia may improve both of these statistics.